Letter to the Editor: Consensus‐based European guidelines for treatment of atopic eczema (atopic dermatitis) in adults and children: part II. (15th January 2019) - Wüthrich, B.; Senti, G.; Kündig, T.M.
Abstract : Linked article: This article is commented on by A. Wollenberg et al ., pp. e153–e154 in this issue. To view this article visithttps://doi.org/10.1111/jdv.15384 .